2016
DOI: 10.1016/j.bioelechem.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of raw and digested pig slurry treatment in bioelectrochemical systems

Abstract: Both raw and anaerobically digested pig slurries were investigated in batch assays in two chambered bioelectrochemical systems (BES) run in Microbial Fuel Cell (MFC) and Microbial Electrolysis Cell (MEC) mode. Chemical Oxygen Demand (COD) removal, nitrogen recovery, cation transport and anode microbial population evolutions were assessed. The Anaerobic Digestion-MEC (AD-MEC) integrated system achieved the highest COD removal (60% in 48h); while the maximum NH4(+) removal efficiency (40%, with an ammonia flux o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 45 publications
(61 reference statements)
6
27
0
Order By: Relevance
“…The former demand of using real wastewater in the studies has been fulfilled and resulted in a better understanding of how to operate such systems. In many cases, the use of real wastewater [139,144,168,173,174,175,176], sewage sludge [152,153], waste activated sludge [177], digested or non-digested slurry [178] was supplemented by other substrates such as glucose [168] or sodium acetate [144] to enhance microorganism growth. Nevertheless, further studies are required to develop strategies for improving the degradation of complex materials and controlling the microbial reactions occurring in the system [25].…”
Section: Applications Of Electromethanogenesismentioning
confidence: 99%
“…The former demand of using real wastewater in the studies has been fulfilled and resulted in a better understanding of how to operate such systems. In many cases, the use of real wastewater [139,144,168,173,174,175,176], sewage sludge [152,153], waste activated sludge [177], digested or non-digested slurry [178] was supplemented by other substrates such as glucose [168] or sodium acetate [144] to enhance microorganism growth. Nevertheless, further studies are required to develop strategies for improving the degradation of complex materials and controlling the microbial reactions occurring in the system [25].…”
Section: Applications Of Electromethanogenesismentioning
confidence: 99%
“…MFCs have recently proven to be a promising technology when combined with anaerobic digestion (AD), mainly as a polishing strategy to increase the quality of the effluent, either by reducing its organic matter content or by removing nutrients . Different kinds of substrates have been used: landfill leachate, wastewater from potato‐processing industries, sludge, pig slurry, a mixture of swine manure and rice bran or molasses wastewater …”
Section: Introductionmentioning
confidence: 99%
“…Aside from the suitability of MFCs as a means to reduce VFAs, they have also been used for ammonia recovery, since in a two‐chambered system a flux of cations travels through the cation exchange membrane, from the anode to the cathode compartment, in order to maintain the system's electroneutrality . A subsequent stripping and absorption step will allow recovered ammonia to be reused as a fertiliser . This application is particularly interesting since AD does not modify the total amount of N in the digestate, and thus needs to be combined with other processes for N removal or recovery, particularly when working with high strength wastewaters such as livestock manure.…”
Section: Introductionmentioning
confidence: 99%
“…The anode was made of carbon felt and the cathode consisted of a piece of stainless steel mesh. The same configuration was previously used by the Authors to compare the improvement of combining AD with a BES working in MFC mode or as an MEC . The results of this work showed that the integration of an MEC with an AD unit allows the whole system to reach a stable COD removal of 46 % while recovering 40 % of ammonia.…”
Section: Bioelectrochemical Systems Fed With Urinementioning
confidence: 69%
“…The same configuration was previously used by the Authors to compare the improvement of combining AD with a BES working in MFC mode or as an MEC. [113] The results of this work showed that the integration of an MEC with an AD unit allows the whole system to reach a stable COD removal of 46 % while recovering 40 % of ammonia. It was observed that the integration of an MEC not only helps to stabilise the AD against organic and nitrogen overloading but also to enhance the quality of the effluent and recover nitrogen in the form of ammonia.…”
Section: Microbial Electrolysis Cell (Mec) Using Urine For Nutrientmentioning
confidence: 79%